ROLE CONTRADICATIONS BETWEEN CONSULTANTS OF ACCOUNTANT SERVICES AND PUBLIC ACCOUNTANT OFFICES - Fitriana Santi; Ary Yunita Anggraeni (Universitas Pamulang, 2019)
Abstract The Office of Accountant Services is an accounting services office that is allowed to provide management services, taxation and assurance service. The thing that distinguishesbetween KJA and KAP is where the Public Accountant Office is allowed to provide assurance and audit services. In practice there was a dualism of work where the services provided by KJA could also be provided by KAP. While the services provided by KAP cannot be provided by KJA. This is what results in the intersection of interests between KAP and KJA. The reason for the struggle for market share is also their basis for fighting over clients. If thiscontinues, they are not impossible to not focus on the quality of services provided. The writing of this article explains the intersection between these two accounting service offices.Where there is a mental accounting theory that is the background of the dispute between these two service offices.